Analisis Pengukuran Pendapatan Sales Berdasarkan PSAK No 72 - Siti Nurhidayah; Abu Darim (Manajemen Kreatif Jurnal, 2023)
Under the guidance of Dr. H. Abu Darim, MPD., MSI supervisor The purpose of this research was to find out whether the method applied by the company PT Timex Indonesia Surabaya in measuring its income was in accordance with the accounting standard statement PSAK No. 72. The method used in this research is a qualitative descriptive method using financial report documents of PT Timex Indonesia Surabaya. The results of this research state that PT Timex Indonesia Surabaya measures income based on the accrual basis concept, where income is recognized after carrying out transactions, but cash payments have not been received. The results of this research conclude that the records used by PT Timex Indonesia Surabaya in measuring its income are in accordance with the accounting standard statement PSAK No. 72.